The European Medicines Agency Review of Brentuximab Vedotin (Adcetris) for the Treatment of Adult Patients With Relapsed or Refractory CD30+ Hodgkin Lymphoma or Systemic Anaplastic Large Cell Lymphoma: Summary of the Scientific Assessment of the Committee for Medicinal Products for Human Use. (30th November 2015) - Gravanis, Iordanis; Tzogani, Kyriaki; van Hennik, Paula; de Graeff, Pieter; Schmitt, Petra; Mueller‐Berghaus, Jan; Salmonson, Tomas; Gisselbrecht, Christian; Laane, Edward; Bergmann, Lothar; Pignatti, Francesco
Abstract : Background: On October 25, 2012, a conditional marketing authorization valid throughout the European Union (EU) was issued for brentuximab vedotin for the treatment of adult patients with relapsed or refractory CD30+ Hodgkin lymphoma (HL) and for the treatment of adult patients with relapsed or refractory systemic anaplastic large cell lymphoma (sALCL). For HL, the indication is restricted to treatment after autologous stem cell transplantation (ASCT) or after at least two previous therapies when ASCT or multiagent chemotherapy is not a treatment option. Materials and Methods: Brentuximab vedotin is an antibody‐drug conjugate (ADC) composed of a CD30‐directed monoclonal antibody (recombinant chimeric IgG1) that is covalently linked to the antimicrotubule agent monomethyl auristatin E (MMAE). Binding of the ADC to CD30 on the cell surface initiates internalization of the MMAE‐CD30 complex, followed by proteolytic cleavage that releases MMAE. The recommended dose is 1.8 mg/kg administered as an intravenous infusion over 30 minutes every 3 weeks. Results: Brentuximab vedotin as a single agent was evaluated in two single‐arm studies. Study SG035‐003 included 102 patients with relapsed or refractory HL. An objective response was observed in 76 patients (75%), with complete remission in 34 (33%). Study SG035‐004 included 58 patients with relapsed or refractory sALCL. An objective response was observed in 50 patients (86%), with complete remission in 34 (59%). The most frequently observed toxicities were peripheral sensory neuropathy, fatigue, nausea, diarrhea, neutropenia, vomiting, pyrexia, and upper respiratory tract infection. Conclusion: The present report summarizes the scientific review of the application leading to approval in the EU. The detailed scientific assessment report and product information, including the summary of the product characteristics, are available on the European Medicines Agency website (http://www.ema.europa.eu ). Implications for Practice: Brentuximab vedotin was approved in the European Union for the treatment of adult patients with relapsed or refractory CD30+ Hodgkin lymphoma or systemic anaplastic large cell lymphoma. For Hodgkin lymphoma, brentuximab vedotin should only be used after autologous stem cell transplantation or following at least two prior therapies when transplantation or multiagent chemotherapy is not a treatment option. In two studies involving 160 patients, partial or complete responses were observed in the majority of patients. Although there was no information on the survival of patients treated in the studies at the time of approval, the responses were considered a clinically relevant benefit. Abstract : Brentuximab vedotin is an antibody‐drug conjugate composed of a CD30‐directed monoclonal antibody covalently linked to the antimicrotubule agent monomethyl auristatin E (MMAE). The recommended dose is 1.8 mg/kg administered as an intravenous infusion over 30 minutes every 3 weeks. The scientific review of the application leading to approval in the European Union is summarized in the present report.